1961
DOI: 10.1017/s0025315400016210
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the biology of limpets IV. The breeding of patella depress a pennant on the north Cornish coast

Abstract: SUMMARYThe breeding of Patella depressa was studied at Trevone, North Cornwall, for 4 years. Gonads were examined and assessed by methods described in a previous report on P. vulgata.In contrast to the common Limpet, P. depressa is a summer breeder in Cornwall. Gonad development begins in the spring and is complete by June or July. Spawning coincides with maximum air temperatures in July, August or early September. The autumn and winter period is passed with gonads in recognizable post-spawning and spent stage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
34
1

Year Published

1986
1986
2005
2005

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 10 publications
3
34
1
Order By: Relevance
“…This is in contrast to what has been described for Patella depressa from exposed and sheltered sites in the centre of Portugal (Cabo Raso, Cascais). Morais et al (2003) found that, in the summer, gametogenesis in limpets from the exposed site was more advanced (mainly stage III and stage IV) than that in limpets from the sheltered site (stage III), according to the maturation scale of Orton et al (1961). The similar reproductive cycles of the two ecomorphs described in this study may reflect phylogenetic preservation of reproductive patterns, as referred to by Henninger and Hodgson (2001).…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…This is in contrast to what has been described for Patella depressa from exposed and sheltered sites in the centre of Portugal (Cabo Raso, Cascais). Morais et al (2003) found that, in the summer, gametogenesis in limpets from the exposed site was more advanced (mainly stage III and stage IV) than that in limpets from the sheltered site (stage III), according to the maturation scale of Orton et al (1961). The similar reproductive cycles of the two ecomorphs described in this study may reflect phylogenetic preservation of reproductive patterns, as referred to by Henninger and Hodgson (2001).…”
Section: Discussionsupporting
confidence: 66%
“…Summer spawning events have been reported for Patella vulgata in NE England (August: Bowman and Lewis, 1986) and in Portugal (September/October: Guerra and Gaudêncio, 1986). P. depressa has also been identified as a summer breeder in Britain (Orton and Southward, 1961) and in Portugal (early summer and early autumn: Guerra and Gaudêncio, 1986). The fact that in P. candei gomesii the levels of gametes remain high until January is not surprising, as P. depressa in the south of Portugal also presents fat and ripe gonads over the winter season (Guerra and Gaudêncio, 1986).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…aspera) of Guerra & Gaudencio (see this volume). They contrast strongly with data from Britain and Ireland (Orton & Southward, 1961;Thompson, 1979;Bowman, 1985;Bowman & Lewis, this volume) where gonad activity is of much shorter duration and usually confined to midsummer and/or early autumn.…”
contrasting
confidence: 81%